Controllable Synthesis of a Compound Based on Hexagonal h-MoO3 Single Crystal and Its Application in Photocatalytic Degradation of Tetracycline

CN116356423BActive Publication Date: 2026-10-09ANYANG NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310125884.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-16
Publication Date
2026-10-09
Estimated Expiration
2043-02-16

AI Technical Summary

Technical Problem

然而该材料详细的晶体结构以及Mo-O键的连接方式还未见报道,目前已报道的h-MoO3材料一般都是纳米级尺寸,很难得到能够测定晶体结构的h-MoO3单晶

Benefits of technology

[0026] (1) This invention relates to the controllable synthesis of a compound based on hexagonal h-MoO3 single crystals and its application in the photocatalytic degradation of tetracycline. The L ligand used has certain acid-base stability and redox activity. The reaction between ligand L and Cu... II The addition of salt resulted in a single-crystal compound 1 based on h-MoO3. In the structure of compound 1, the metal center Mo adopts an irregular 6-coordination configuration to connect the corresponding oxygen atoms to form a three-dimensional crystal structure and exhibits good photodegradation performance for tetracycline.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116356423B_ABST
    Figure CN116356423B_ABST
Patent Text Reader

Abstract

This invention discloses a controllable synthesis of a compound based on hexagonal h-MoO3 single crystals and its application in photocatalytic degradation of tetracycline, comprising the following steps: Step 1: Synthesizing pyridinecarboxaldehyde dihydrated hydrazine ligand L; Step 2: Weighing a quantitative amount of L, (NH4)6Mo7O 24 • Compound 1, a compound based on hexagonal h-MoO3 single crystals, was prepared by reacting 4H2O and CuCl2·2H2O in a reaction vessel under hydrothermal conditions. The L ligand used possesses certain acid-base stability and redox activity. The reaction was carried out via the interaction of ligand L and Cu... II The addition of salt regulated the formation of a single-crystal compound 1 based on h-MoO3. In the structure of compound 1, the metal center Mo adopts an irregular 6-coordination configuration to connect the corresponding oxygen atoms to form a three-dimensional crystal structure and exhibits good photodegradation performance of tetracycline.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalysis technology, specifically relating to a method for preparing a hexagonal h-MoO3 single crystal compound and its application in photocatalytic degradation of tetracycline. Background Technology

[0002] Antibiotics, due to their ability to treat bacterial infections and protect human health, have become a widely used class of drugs worldwide. However, the overuse of antibiotics causes many serious environmental problems. Residual antibiotics can be detected in plants, water resources, and food, posing a significant threat to human health and organic life in the ecosystem. For example, tetracycline molecules, due to their excellent water solubility, chemical stability, and non-volatility, can cause irreversible damage to plants, animals, and humans. Therefore, developing materials to achieve the chemical degradation of these molecules is particularly important. Photodegradation technology, which uses light sources such as sunlight to convert light energy into chemical energy to achieve the chemical degradation of organic matter, has received widespread attention due to its effective cleaning properties and lack of secondary pollution. In this field, developing a low-cost, highly active, and long-life photocatalyst has been a hot research topic for scientists.

[0003] MoO3, a traditional inorganic semiconductor material, has wide applications in photochromism, electrochemistry, supercapacitors, and catalysis due to the unique electronic structure of the Mo core. Common MoO3 structures include three main types: orthorhombic (α-MoO3), monoclinic (β-MoO3), and hexagonal (h-MoO3). The hexagonal h-MoO3, with its narrow bandgap and high chemical reactivity, has been a focus of research. However, its detailed crystal structure and Mo-O bond configuration remain unreported. Currently reported h-MoO3 materials are generally nanoscale, making it difficult to obtain h-MoO3 single crystals with measurable crystal structures.

[0004] Therefore, designing an h-MoO3 with a specific crystal structure to achieve visible light degradation of tetracycline is of great significance in both the field of inorganic functional materials and the environmental field. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a controllable synthesis of compounds based on hexagonal h-MoO3 single crystals and their application in photocatalytic degradation of tetracycline, thereby enabling h-MoO3 to degrade tetracycline under visible light.

[0006] This invention provides the following technical solution:

[0007] A controllable synthesis method for compounds based on hexagonal h-MoO3 single crystals includes the following steps:

[0008] Step 1: Synthesize pyridinecarboxaldehyde bis-glycidylamine ligand L;

[0009] Step 2: Weigh out a fixed amount of L, (NH4)6Mo7O 24 Compounds based on hexagonal h-MoO3 single crystals were prepared by placing ·4H2O and CuCl2·2H2O in a reaction vessel under hydrothermal conditions.

[0010] Preferably, in step one, the specific method for synthesizing the pyridinecarboxaldehyde dihydrate hydrazine ligand L is as follows:

[0011] S1. Weigh a certain amount of 4-pyridinecarboxaldehyde and dissolve it in ethanol;

[0012] S2. Dissolve hydrazine hydrate in ethanol and add it dropwise to the solution obtained in S1 under stirring;

[0013] S3. Stir the mixture in S2 at room temperature, filter, wash and dry to obtain yellow powder ligand L.

[0014] Preferably, in step one, the specific method for synthesizing the pyridinecarboxaldehyde dihydrate hydrazine ligand L is as follows:

[0015] S1. Weigh 4-pyridinecarboxaldehyde (4.28 g, 40 mmol) and dissolve it in 7.5 mL of ethanol;

[0016] S2. Dissolve 1 mL of hydrazine hydrate (21 mmol) in 7.5 mL of ethanol and add it dropwise to the S1 solution while stirring.

[0017] S3. Stir the mixture in S2 at room temperature for 20 minutes, filter, wash and dry to obtain yellow powder ligand L.

[0018] Preferably, in step two, the specific method for obtaining the compound based on hexagonal h-MoO3 single crystal is as follows:

[0019] A1、(NH4)6Mo7O 24 ·4H2O, L and CuCl2·2H2O were placed in the lining of the reaction vessel, and ethanol, H2O and HCl aqueous solution were added, and then stirred at room temperature.

[0020] A2. Transfer the liner to a stainless steel reactor, heat it in an oven at 100-140℃, and cool it to room temperature. Open the reactor to obtain a green single crystal, which is the compound based on hexagonal h-MoO3 single crystal.

[0021] Preferably, in step two, the specific method for obtaining the compound based on hexagonal h-MoO3 single crystal is as follows:

[0022] A1. Weigh out (NH4)6Mo7O24 ·4H2O (0.15g), L (0.021g) and CuCl2·2H2O (0.050g) were placed in the lining of the reaction vessel, and ethanol (4mL), H2O (4mL) and HCl aqueous solution (1mol / L, 200μL) were added. The mixture was stirred at room temperature for 2h.

[0023] A2. Transfer the liner to a stainless steel reactor, heat it in an oven at 120°C for 3 days, and then cool it to room temperature. Open the reactor to obtain a green single crystal, which is the compound based on hexagonal phase h-MoO3 single crystal.

[0024] Preferably, the application of compounds based on hexagonal h-MoO3 single crystals in the catalytic degradation of tetracycline under visible light irradiation.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) This invention relates to the controllable synthesis of a compound based on hexagonal h-MoO3 single crystals and its application in the photocatalytic degradation of tetracycline. The L ligand used has certain acid-base stability and redox activity. The reaction between ligand L and Cu... II The addition of salt resulted in a single-crystal compound 1 based on h-MoO3. In the structure of compound 1, the metal center Mo adopts an irregular 6-coordination configuration to connect the corresponding oxygen atoms to form a three-dimensional crystal structure and exhibits good photodegradation performance for tetracycline. Attached Figure Description

[0027] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained from these drawings without creative effort.

[0028] Figure 1 The PXRD pattern of compound 1 prepared according to the present invention;

[0029] Figure 2 IR spectrum of compound 1;

[0030] Figure 3 Thermogravimetric analysis spectrum of compound 1;

[0031] Figure 4 The solid-state UV-Vis absorption spectrum of compound 1;

[0032] Figure 5 Mo of compound 1 VI Coordination environment diagram;

[0033] Figure 6 Structural diagram of the secondary building block [Mo3O6] in compound 1;

[0034] Figure 7 One-dimensional chain diagram of compound 1;

[0035] Figure 8 Three-dimensional structural diagram of compound 1;

[0036] Figure 9 XPS spectrum of compound 1;

[0037] Figure 10 The UV-Vis absorption spectrum of the tetracycline solution catalyzed by compound 1;

[0038] Figure 11 Degradation rate curves of compound 1 and comparative experiments;

[0039] Figure 12 Photocurrent spectra of compound 1 and purchased MoO3;

[0040] Figure 13 AC impedance spectra of compound 1 and purchased MoO3;

[0041] Figure 14 Cycle curve of catalytic degradation of tetracycline by compound 1;

[0042] Figure 15 Bar graph of degradation rate of compound 1 under BQ, IPA and EDTA conditions;

[0043] Figure 16 Mass spectrum of tetracycline solution after reaction;

[0044] Figure 17 Tetracycline degradation route map;

[0045] Figure 18 Crystal data sheet for compound 1;

[0046] Figure 19 Partial bond length and bond angle data for coordination compound 1. Detailed Implementation

[0047] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0048] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.

[0049] Example 1:

[0050] A method for preparing compound 1 based on hexagonal h-MoO3 single crystal includes the following steps:

[0051] Step 1: Synthesis of pyridinecarboxaldehyde bis-glycidylamine ligand (L);

[0052] Step 2: Weigh out a fixed amount of L, (NH4)6Mo7O 24 The target compound 1, namely the compound based on hexagonal phase h-MoO3 single crystal, was prepared by placing ·4H2O and CuCl2·2H2O in a reaction vessel under hydrothermal conditions.

[0053] The specific steps are as follows:

[0054] 1) Weigh 4-pyridinecarboxaldehyde (4.28 g, 40 mmol) and dissolve it in 7.5 mL of ethanol;

[0055] 2) Dissolve 1 mL of hydrazine hydrate (21 mmol) in 7.5 mL of ethanol and add it dropwise to the above solution while stirring;

[0056] 3) Stir the mixture at room temperature for 20 minutes, filter, wash and dry to obtain yellow powder ligand L.

[0057] Furthermore, the synthesized L-ligand is used in the method of constructing compound 1 as follows:

[0058] 1) Weigh out (NH4)6Mo7O 24 ·4H2O (0.15g), L (0.021g) and CuCl2·2H2O (0.050g) were placed in the lining of the reaction vessel, and ethanol (4mL), H2O (4mL) and HCl aqueous solution (1mol / L, 200μL) were added. The mixture was stirred at room temperature for 2h.

[0059] 2) Transfer the liner to a stainless steel reactor, heat it in an oven at 120°C for 3 days, and then cool it to room temperature. Open the reactor to obtain green single crystals, which are compound 1.

[0060] Example 2

[0061] Application of the synthesized complex 1 in the catalytic degradation of tetracycline under visible light irradiation.

[0062] Example 3

[0063] The reagents, instruments, and characterization methods used in the experiments of this invention are as follows:

[0064] Experimental drugs

[0065] The CuCl2·2H2O, ethanol, and (NH4)6Mo7O used in the experiments of this invention 24 • 4H2O, 4-pyridinecarboxaldehyde, and hydrazine hydrate were all analytical grade reagents purchased from Shanghai Titan Technology Co., Ltd., and were not purified before use.

[0066] Characterization instruments

[0067] The powder diffraction peaks (PXRD) of the prepared samples were analyzed using an X'Pert PRO MPD X-ray powder diffractometer from PANalytical (Netherlands). The crystal structure of complex 1 was determined using a SMART APEX-II X-ray single-crystal diffractometer from Bruker (Germany). The single-crystal structure of complex 1 was resolved using the least squares method with SHELXS-97 and SHELXL-97 software. The valence state of the Mo centers in the prepared compounds was analyzed using X-ray photoelectron spectroscopy (XPS, ThermoFisher α+), with the signal of carbon with a binding energy of 284.8 eV as a reference. The infrared spectrum (IR) of complex 1 was measured using an iS50 infrared spectrometer from Nicolet (USA). Thermogravimetric analysis (TG) of complex 1 was performed using a STA-449F3 analyzer from Netzsch (Germany). The intermediate products of tetracycline degradation were detected using a Waters LCT Premier XE liquid chromatography-mass spectrometry (LC-MS) system from Waters (USA). The solid-state UV-Vis absorption spectra of the samples were characterized using a Shimadzu UV-2550 UV spectrophotometer, with barium sulfate absorbance used as a reference. The photodegradation process was performed using a multi-parallel reactor with a 500W xenon lamp as the light source. The absorbance of the tetracycline solution during degradation was measured using a Cary 60 UV-Vis spectrophotometer.

[0068] Electrochemical testing

[0069] Electrochemical tests of Compound 1 were performed using a CHI-760E (Shanghai Chenhua) electrochemical workstation. I / FTO or MoO3 / FTO was selected as the working electrode, an Ag / AgCl electrode containing saturated potassium chloride solution was used as the reference electrode, and a platinum sheet electrode was used as the auxiliary electrode. The working electrode was prepared as follows: Compound 1 or purchased MoO3 (3.0 mg) was weighed and added to 1.0 mL of ethanol. 20.0 μL of Nafion solution was added to the above solution using a pipette and ultrasonically vibrated for 30 min. 50.0 μL of the mixture was then dropped onto a conductive glass (FTO), exposing a working area of ​​1.0 cm² to the electrolyte. 2The electrolyte used in the test was a 0.2 mol / L Na₂SO₄ solution (pH = 7). The photocurrent was tested with a bias voltage of 0.2 V (using a 300 W xenon lamp as the light source), and the AC impedance was tested with a bias voltage of 2.0 V.

[0070] Tetracycline degradation test

[0071] The photocatalytic degradation of tetracycline by compound 1 was conducted on a multi-parallel reactor at room temperature. 5 mg of powder sample was uniformly dispersed in 30 mL of tetracycline solution (30 mg / L) and magnetically stirred in the dark for 30 min to reach adsorption-desorption equilibrium. A xenon lamp was turned on, and 3 mL of solution was taken every 30 min. The supernatant was collected by centrifugation and analyzed using a UV-Vis spectrophotometer. The absorption intensity of the characteristic peak around 368 nm was used as the basis for calculating the tetracycline degradation rate.

[0072] 1. PXRD and IR characterization

[0073] The phase purity of compound 1 was verified by X-ray powder diffraction (PXRD). The theoretical and experimental PXRD values ​​of compound 1 were almost identical. Figure 1 This indicates that the synthesized compound 1 is a single pure phase. Further comparison with the characteristic peak cards of h-MoO3 confirms that the obtained single-crystal compound is hexagonal h-MoO3. In the infrared (IR) spectrum of compound 1, two peaks are located at 521 and 609 cm⁻¹. -1 The characteristic vibration peaks are attributed to the stretching and bending vibrations of O-Mo-O. Figure 2 Located at 911 and 974 cm. -1 The vibration peaks are attributed to the stretching vibrations of the Mo=O bonds.

[0074] 2. Characterization by TG and solid-state UV-Vis absorption spectroscopy

[0075] The thermal stability of the prepared compound 1 was analyzed using a thermogravimetric analyzer. For example... Figure 3 As shown, complex 1 maintained good stability in the temperature range of 40-330℃. Subsequently, it exhibited significant weight loss, which is attributed to the decomposition of the compound 1 structure. The optical properties of complex 1 were further investigated using solid-state UV-Vis spectroscopy. Figure 4 As shown, compound 1 exhibits a good absorption peak in the 200-440 nm range. Compared with the purchased MoO3, compound 1 has a stronger absorption peak intensity in the visible region and exhibits better light absorption performance.

[0076] 3. Single-crystal structure characterization and XPS analysis of compound 1

[0077] Single-crystal analysis of complex 1 was performed using a Bruker SMART APEX-II single-crystal diffractometer. Tables 1 and 2 list the crystallographic data and partial bond length and bond angle data of compound 1, respectively. Compound 1 crystallizes in the hexagonal crystal system, space group P63 / m (Table 1), with the smallest asymmetric unit containing 0.5 Mo centers and 1.5 coordinated O atoms.

[0078] like Figure 5-7 As shown, compound 1 contains 0.5 independent Mo atoms. VI At the center, the Mo1 atom coordinates with six O atoms (O1, O2, O3, O1A, O1B, O2C), forming an irregular octahedral coordination configuration. Figure 5 The Mo-O bond length and O-Mo-O bond angle range from 1.703(4) to 2.355(5). And 74.22(14)-175.0(2)° (Table 2). On the one hand, three adjacent Mo centers are connected by three μ2-O2 bridges to form a triangular-like secondary building unit [Mo3O6]( Figure 6 On the other hand, μ3-O1 connects three adjacent Mo centers, forming a ladder-shaped one-dimensional chain along the c-axis, where the distances between Mo…Mo are 3.3095(7) and 3.7184(7), respectively. The distance between Mo…Mo is 4.0127(9). ( Figure 7 Adjacent [Mo3O6] units are further connected by c-axis one-dimensional chains to form a three-dimensional framework structure. Figure 8 To further determine the valence state of the Mo center in compound 1, XPS analysis was performed. Figure 9 As shown, compound 1 exhibits distinct characteristic peaks at 236.1 eV and 233.0 eV, which are attributed to Mo, respectively. VI 3D 3 / 2 and 3D 5 / 2 The binding energy of the orbital electrons. This further proves that the Mo center in metal has a +6 valence and is completely consistent with the single-crystal analysis results.

[0079] 4. Research on the degradation of tetracycline

[0080] We conducted a photodegradation experiment on compound 1 of tetracycline under room temperature conditions, and calculated the degradation rate by the absorbance at 368 nm, where the degradation rate = (1-C) / (2π) = 1 / 2π * (C / 2π) ... t / C0)×100%, C t C and C0 represent the concentrations at time t and the initial time, respectively. The test results are as follows: Figure 7 As shown, in the presence of compound 1, the intensity of the tetracycline characteristic peak continuously decreased with increasing reaction time, and the degradation rate reached as high as 80.0% after 120 minutes of reaction. Figure 10 , Figure 11 By comparing with a blank experiment, the degradation rate of tetracycline without compound 1 was 17.3%; further adjustment of reaction conditions, the degradation rate of compound 1 under dark conditions was only 3.9%. This indicates that the addition of compound 1 and light conditions play important roles in the degradation of tetracycline. Compared with the purchased MoO3 (degradation rate of 35.1%), compound 1 exhibits excellent photocatalytic degradation performance. Photocurrent testing revealed that compound 1 exhibits a higher photocurrent signal, indicating that compound 1 has a stronger photoinduced electron-hole separation ability than the purchased MoO3. Figure 12 Further measurements of its AC impedance spectrum revealed that compound 1 exhibited a smaller radius, indicating that the surface compound possessed lower carrier transport resistance. Figure 13 These results are of great significance in the photocatalytic reaction process. X-ray powder diffraction analysis of complex 1 after the reaction revealed that the diffraction peaks of complex 1 after the reaction were essentially consistent with those before the reaction. Figure 1 This indicates that complex 1 exhibits good structural stability during the catalytic process. Further analysis of the XPS spectrum of compound 1 after the reaction... Figure 9 ), discovered Mo VI The binding energy at the center shifted by 0.2 eV towards the smaller value, indicating that Mo VI The central d electrons play a crucial role in the photocatalytic process. Further analysis of the recovered compound 1 in its cyclic degradation of tetracycline revealed that the degradation rate of complex 1 increased from 80.0% in the first round to 79.8% in the second round, and further to 80.2% in the third round. Figure 14 This indicates that compound 1 has good catalytic cycling performance and its catalytic activity remains stable.

[0081] To further investigate the reaction mechanism, p-benzoquinone (BQ), isopropanol (IPA), and sodium ethylenediaminetetraacetate (EDTA) were selected as ·O2, respectively. - Free radicals, ·OH radicals, holes (h + Quenching experiments were conducted using BQ (0.5 mmol·L⁻¹) and quenchers. The study found that the addition of BQ (0.5 mmol·L⁻¹) resulted in quenching. -1 ) or IPA (5 mmol·L -1 ) or EDTA (0.5 mmol·L -1 In the quenching experiment, the degradation rates of tetracycline were 25.3%, 79.0%, and 31.8%, respectively. Figure 15 This indicates that O2 - Free radicals and holes (h + Compound 1 is the main active component in the catalytic degradation of tetracycline. Therefore, the reaction mechanism can be deduced as follows: 1) Holes (h) generated by photoexcitation of compound 1 + ) and electron e- 2) Electrons react with O2 dissolved in the solution to generate ·O2. - Free radicals, 3) Holes (h + ) and O2 - Free radicals react with tetracycline to generate degradation products.

[0082] 5. Degradation product research

[0083] The reaction solution was then analyzed by liquid chromatography-mass spectrometry. Figure 16 ), and deduced two degradation pathways of tetracycline ( Figure 17 1) Tetracycline (TC) is hydroxylated and N-methyl dehydrogenation to produce product 1 (m / z = 475). Product 1 is further oxidized to product 2 (m / z = 453) by dealdehyde group removal and carbonyl hydrogenation. Product 2 is further oxidized to products 3-6 (3: m / z = 126, 4: m / z = 183, 5: m / z = 142, 6: m / z = 150) through C / C bond cleavage and other reactions. 2) Tetracycline (TC) is demethylated and hydroxylated to produce product 7 (m / z = 434). Product 7 is dehydroxylated and amide group removed to produce product 8 (m / z = 340). Product 8 is further oxidized to products 9-12 (9: m / z = 224, 10: m / z = 208, 11: m / z = 138, 12: m / z = 188) through C / C bond cleavage and other reactions. Product 12 is further oxidized to produce product 13 through dehydrogenation and hydroxyl elimination reactions.

[0084] in conclusion

[0085] (NH4)6Mo7O 24 Using 4H2O, pyridinecarboxaldehyde bis(glycidyl)-amine ligand L, and CuCl2·2H2O as raw materials, a single-crystal compound 1 based on h-MoO3 was successfully prepared under solvothermal conditions. The degradation rate of tetracycline under visible light was tested, and compound 1 showed a degradation rate of 80.0% and exhibited good catalytic cycling characteristics. XPS spectral analysis of compound 1 after the reaction revealed that Mo... VI The central d electrons play a crucial role in the reaction process. This study demonstrates the catalytic degradation of tetracycline by the single-crystal structure of hexagonal h-MoO3 under visible light irradiation and its possible degradation pathway, providing a theoretical basis for the development of high-performance photodegradation of organic pollutants.

[0086] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention can have various modifications and variations; any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A controllable synthesis method for compounds based on hexagonal h-MoO3 single crystals, characterized in that, Includes the following steps: Step 1: Synthesize pyridinecarboxaldehyde bis-glycidylamine ligand L; Step 2: Weigh out a specific amount of pyridine carboxaldehyde dihydrated hydrazine ligand L, (NH4)6Mo7O 24 ·4H2O and CuCl2·2H2O were placed in the lining of a reaction vessel, and ethanol, H2O and HCl aqueous solution were added. The mixture was then stirred at room temperature. The lining was transferred to a stainless steel reaction vessel, heated in an oven at 100-140 °C, and cooled to room temperature. The reaction vessel was then opened to obtain a green single crystal, which is the compound based on the hexagonal phase h-MoO3 single crystal. The compound based on the hexagonal phase h-MoO3 single crystal crystallizes in the hexagonal crystal system P63 / m space group, and its smallest asymmetric unit contains 0.5 Mo centers and 1.5 coordinated O atoms. In step one, the specific method for synthesizing the pyridinecarboxaldehyde dihydrate hydrazine ligand L is as follows: S1. Weigh a certain amount of 4-pyridinecarboxaldehyde and dissolve it in ethanol; S2. Dissolve hydrazine hydrate in ethanol and add it dropwise to the solution obtained in S1 under stirring; S3. Stir the mixture in S2 at room temperature, filter, wash and dry to obtain yellow powder pyridinecarboxaldehyde dihydrated ligand L.

2. The controllable synthesis method of a compound based on hexagonal h-MoO3 single crystal according to claim 1, characterized in that, In step one, the specific method for synthesizing the pyridinecarboxaldehyde dihydrate hydrazine ligand L is as follows: S1. Weigh 4.28 g (40 mmol) of 4-pyridinecarboxaldehyde and dissolve it in 7.5 mL of ethanol. S2. Measure 1 mL of hydrazine hydrate (21 mmol); dissolve it in 7.5 mL of ethanol and add it dropwise to the S1 solution under stirring. S3. Stir the mixture in S2 at room temperature for 20 min, filter, wash and dry to obtain yellow powder pyridinecarboxaldehyde dihydrate ligand L.

3. The controllable synthesis method of a compound based on hexagonal h-MoO3 single crystal according to claim 1, characterized in that, In step two, the specific method for obtaining the compound based on hexagonal h-MoO3 single crystal is as follows: A1. Weigh out 0.15g of (NH4)6Mo7O 24 ·4H2O, 0.021 g of pyridinecarboxaldehyde dihydrated hydrazine ligand L and 0.050 g of CuCl2·2H2O were placed in the liner of the reaction vessel, and 4 mL of ethanol, 4 mL of H2O and 200 μL of HCl aqueous solution (1 mol / L) were added. The mixture was stirred at room temperature for 2 h. A2. Transfer the liner to a stainless steel reactor, heat it in an oven at 120 °C for 3 days, and then cool it to room temperature. Open the reactor to obtain a green single crystal, which is the compound based on the hexagonal phase h-MoO3 single crystal.

4. An application of a compound based on the hexagonal h-MoO3 single crystal as described in any one of claims 1-3, characterized in that, The compound based on hexagonal h-MoO3 single crystal is used for the catalytic degradation of tetracycline under visible light irradiation. The compound based on hexagonal h-MoO3 single crystal is a green single crystal, crystallized in the hexagonal crystal system P63 / m space group, and its smallest asymmetric unit contains 0.5 Mo centers and 1.5 coordinated O atoms.

Citation Information

Patent Citations

  • Polyacid-based metal organic hybrid material as well as preparation method and application thereof

    CN108997441A